Kritik Sosial dalam Naskah Drama West Side Story karya Arthur Laurents: Kajian Sosiologi Sastra - Devy Kurnia Alamsyah; Widya Husein; Yenni Hayati (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
Literary works are often used as a medium to criticize and explain social problems experienced by society. One of these literary works is the drama script West Side Story by Arthur Laurenst. This study focuses on the criticism of several social problems described in the play West Side Story. This study uses the method of content analysis of literary texts which are then interpreted by researchers. Research data sourced from the play West Side Story was collected using the library research method. Through analysis with the Sociology of Literature approach which focuses on sociological aspects in a work, it is found that there is a critique of social problems described in the play West Wide Story. The criticism is related to the problem of poverty which leads to violence and deprivation; juvenile delinquency in the form of immoral acts as a result of family disharmony; wars that cause damage to the natural environment; and degrading and harassing women.